Menelisik Conscientiousness dan Toleransi Ambiguitas terhadap Kecenderungan Pengambilan Resiko pada Pelaku UMKM di Era New Normal - Mardhiyah, Sayang Ajeng; Rezkyandar, Muhammad (UIN Sunan Kalijaga, 2024)
In challenging situations like the Covid-19 pandemic, MSME entrepreneurs are among the affected parties. However, the development and efforts to recover have become a primary demand for MSME entrepreneurs to survive in difficult circumstances. Coupled with changes in consumer habits and preferences, known as the